Dermoscopy examination of petechial lesions in a patient with Dermatitis Herpetiformis - Paulo Ricardo Criado; Nilton Gioia Di Chiacchio; Leopoldo Duailibe Nogueira Santos (Sociedade Brasileira de Dermatologia, 2013)
An uncommon skin manifestation of Dermatitis Herpetiformis is palmar and plantar purpura. Dermoscopic examination is useful for any skin condition since it allows recognition of structures that are not discernible to the naked eye. A 22 year-old Caucasian man was admitted with excoriated lesions and pruritus. Petechial lesions could be seen on volar aspect of the digits on the hands and feet. Dermoscopy examination revealed erythematous and violaceous dots and erythematous and brown dots.